Managing Private Primary Schools in Bangkok for Excellence - Petchnoi, Tanabordee; Kaewmongkol, Songyot; Kareevate, Somnuk (Arts of Management Journal, 2023)
This research has three objectives: 1) to analyze the components of private primary school administration in Bangkok towards excellence; 2) to study the management of private primary schools in Bangkok; and 3) to try and evaluate the management approach of private primary schools in Bangkok towards excellence. The population in this research was divided into 3 groups. Administrators of private primary schools in Bangkok, the second group, 5 experts, and the third group, 10 users, used 3 research tools: questionnaires, interviews, and interviews using assessments. Percentage, mean, standard deviation, and content analysis. The results of the study found that 1) the elements of management of private primary schools in Bangkok for excellence were 7 components: personnel development, academic and moral activities, learner-centered, leadership Involvement of Network Partners Management of Excellence and Curriculum Management 2) Guidelines for managing private primary schools in Bangkok towards excellence are divided into 4 parts: Part 1: The leading part consists of the principles and objectives of the guideline. Part 2, the content section, includes: Elements of guidelines for the management of private primary schools in Bangkok towards excellence consists of 7 approaches and 39 methods, Part 3: Conditions of Success and Part 4: Consequences of Compliance with the Private Primary School Management Guidelines in Bangkok, and 3) The results of the approach trial and feasibility assessment were the most average overall. In summary, this approach can be used as a guideline for the management of other private primary schools in Thailand.